Clarification of the taxonomic and nomenclatural confusions with three Gynura names (Asteraceae: Senecioneae) based on Zollinger’s collections from Java, Indonesia - Zhu, Li-Cui; Hariri, Muhammad Rifqi; Li, Cheng-Sheng; Ren, Chen (Phytotaxa, 2025)
Gynura mollis, G. lyrata, and G. densiflora (Asteraceae: Senecioneae) were originally based on Zollinger’s collections from Java, Indonesia, but their identities have long been a source of confusion. In this study, we located their type material and clarify their identities. Our findings show that G. densiflora and G. mollis are conspecific with G. ajakensis, and G. mollis, with the priority, is revealed to be the correct name for this species. Gynura lyrata is conspecific with G. aurantiaca and is treated as a synonym of the latter. In addition, we clarified the cross-labelling issue among three Zollinger gatherings: HZ.442, HZ.606, and H.2592. The issue was caused by Zollinger’s specimen-numbering method and has led to significant nomenclatural and taxonomic confusions. This is also an important reminder to researchers working with Zollinger’s collections. Lastly, G. aurantiaca var. ovata is here synonymized with G. mollis, and lectotypes are designated for G. aurantiaca var. ovata, G. densiflora, and G. mollis.